A Comprehensive Literature Review on the Pandemic Coronavirus Disease 2019 (COVID-19) (Bangladesh Journal of Medicine, 2020)
Background: A large number of patient developed pneumonia of unknown cause in the capital cityWuhan of Hubei province in China during the month of Dec 2019, with clinical presentations greatlyresembling viral pneumonia while some rapidly progressed to severe illness and fatal outcome. InternationalCommittee on Taxonomy of Viruses (ICTV) named the virus severe acute respiratory syndrome coronavirus2 (SARS-CoV-2) and WHO officially named the disease COVID-19. World Health Organization (WHO) onJanuary 30 declared the outbreak as a public health emergency of international concern due to rapidglobal spread. On 11 February 2020, WHO announced that “COVID-19” (meaning coronavirus disease-2019) will be the official name of the disease. This report reviews the genetic structure, infection source,transmission route, pathogenesis, clinical characteristics, and treatment and prevention of the SARS-CoV-2, so that it can provide references for follow-up research, prevention and treatment, and may helpreaders to have the latest understanding of this new infectious disease. Information have been gatheredmainly from relevant researches and papers that were published recently.Methods: For this narrative review, more than 50 relevant scientific articles and reports wereconsidered from various databases (e.g., Google Scholar, PubMed and Science Direct) using keywordssuch as SARS-CoV-2; COVID-19; coronavirus; pneumonia; respiratory infectionResults: The results from this review show that the situation is rapidly evolving, as human-to-humantransmission is occurring, and the number of new cases and mortalities is increasing by the day andon a global level. There is still ambiguity about mutation risks and how the virus spreads as thesource was not yet identified. Major gaps in knowledge about the origin of the virus, epidemiologyand transmission impose a great challenge, which emphasizes the need for further studies in thefuture.Conclusion: There are neither vaccines nor effective treatments for the disease caused by the virus,but efforts are typically confined to symptomatic and supportive management. Antivirals andcorticosteroids were used in severe illness but had no effective outcome.Bangladesh J Medicine July 2020; 31(2) :94-101